How do you convert r=3theta - csctheta r=3θcscθ to Cartesian form?

1 Answer
Mar 14, 2016

sqrt(x^2+y^2)=3arctan(y/x)-sqrt(x^2+y^2)/yx2+y2=3arctan(yx)x2+y2y

Explanation:

(r,theta)(r,θ) in polar coordinates is (rcostheta,rsintheta)(rcosθ,rsinθ) in rectangular coordinates and

(x,y)(x,y) in rectangular coordinates is (sqrt(x^2+y^2),arctan(y/x))(x2+y2,arctan(yx)) in polar coordinates.

Note that sintheta=y/r=y/(sqrt(x^2+y^2)sinθ=yr=yx2+y2

Hence r=3theta-cscthetar=3θcscθ can be written as

sqrt(x^2+y^2)=3arctan(y/x)-sqrt(x^2+y^2)/yx2+y2=3arctan(yx)x2+y2y